Motivation and Management: Flexibility of the Implementation of Motivation Theories in Pesantren Context - Ahmad Ta'rifin (Postgraduate Program, Universitas Islam Negeri (UIN) K. H. Abdurrahman Wahid Pekalongan, Indonesia, 2018)
Motivation is viewed as the driving force that is employed to strengthen individuals for improving their performance so as to achieve well-established organizational goals. It is necessary to note that this driving force results from both intrinsic and extrinsic factors. Motivation theories, which were derived from Western countries, have been examined its implementation in business, industry, and education organizations there. Nonetheless, Robbins asserts that the motivation theories are not strictly implemented in the other half of the world. For instance, an educational institution such as pesantren (Islamic boarding school), whose organizational culture is much different from a formal one, has flexibly applied those theories of motivation. It can be noticed that the implementation of Abraham Maslow’s Hierarchy Theory and McClelland’s Needs Theory extremely depends on intellectual capital and organizational culture aspects of the pesantren.